2022
DOI: 10.1038/s41467-022-30702-z
|View full text |Cite
|
Sign up to set email alerts
|

Iron atom–cluster interactions increase activity and improve durability in Fe–N–C fuel cells

Abstract: Simultaneously increasing the activity and stability of the single-atom active sites of M–N–C catalysts is critical but remains a great challenge. Here, we report an Fe–N–C catalyst with nitrogen-coordinated iron clusters and closely surrounding Fe–N4 active sites for oxygen reduction reaction in acidic fuel cells. A strong electronic interaction is built between iron clusters and satellite Fe–N4 due to unblocked electron transfer pathways and very short interacting distances. The iron clusters optimize the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
190
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(201 citation statements)
references
References 72 publications
10
190
1
Order By: Relevance
“…As shown in Fig. S3a,† the peaks of the N and Fe atoms were located at 400 eV and 710 eV for Fe/Fe-NC-3, 36 respectively, matching well with the aforementioned elemental mapping, while the peaks for Fe atoms were not detected for Fe-NC-3 due to the tiny amount of iron atoms. As summarized in Fig.…”
Section: Resultssupporting
confidence: 80%
“…As shown in Fig. S3a,† the peaks of the N and Fe atoms were located at 400 eV and 710 eV for Fe/Fe-NC-3, 36 respectively, matching well with the aforementioned elemental mapping, while the peaks for Fe atoms were not detected for Fe-NC-3 due to the tiny amount of iron atoms. As summarized in Fig.…”
Section: Resultssupporting
confidence: 80%
“…2a) for the Pt@Fe-NC catalyst clearly distinguishes four bands of graphitic N (403.8 eV), pyrrolic N (400.2 eV), Fe-N x (398.5 eV) and pyridine N (397.7 eV), which shows that Fe doped ZIF@PDA precursors were effectively transformed into Fe-NC supports aer pyrolysis. 40,41 Meanwhile, combined with the high-resolution Fe 2p spectrum (Fig. 2b) for Pt@Fe-NC showing three pairs of doublets assigned to Fe 2+ , Fe 3+ , and Fe satellites, respectively, it can be further conrmed that the Fe ions were successfully doped into the carbon support, which is in accordance with the conclusions of TEM.…”
Section: Resultssupporting
confidence: 79%
“…24,26,27 In addition, it is reported that the electronic structure of single-atom sites can be also modified by the existence of the atomic clusters nearing these single-atom sites. 28 enhanced ORR activity. 29 As a result, it is feasible to enhance the catalytic activity of the SA-Fe−N−C catalyst with numerous N−Fe−N 4 moieties near atomic Fe clusters.…”
Section: Introductionmentioning
confidence: 95%
“…Also, the most reported SA-Fe–N–C catalysts are always with Fe–N 4 moieties, especially SA-Fe–N–C, by using ZIF as the precursors. However, the five-coordinated Fe–N 5 moieties that have a Fe–N 4 planar structure with a vertically bonded N atom are considered to exhibit higher ORR activity compared to that of Fe–N 4 species. With this axial N atom, the central Fe atom is dragged out of the carbon basal plane, resulting in a change in the spin state of 3d electrons from low to high due to the redistribution of six electrons in the 3d orbitals of Fe atoms. Also, the adsorption of oxygen-containing intermediates on the central Fe atoms with σ-type bonding would be greatly modulated during the ORR process. Thus, the generated *OH intermediates on the central metal atom can pull the central Fe back into the N 4 plane and convert the spin state of Fe centers from high back to low, eventually reducing the energy barrier for the ORR process. ,, In addition, it is reported that the electronic structure of single-atom sites can be also modified by the existence of the atomic clusters nearing these single-atom sites . For example, Huang et al reported that a Fe cluster-decorated SA-Fe–N–C catalyst with a unique electronic configuration, which shows that the redistribution of electrons on Fe–N 4 centers induced by atomic clusters exhibits an enhanced ORR activity .…”
Section: Introductionmentioning
confidence: 99%